2004
DOI: 10.1196/annals.1318.014
|View full text |Cite
|
Sign up to set email alerts
|

Transrenal DNA as a Diagnostic Tool: Important Technical Notes

Abstract: A small portion of DNA from apoptotic cells escapes complete degradation, appears in blood as oligonucleosomal-size fragments, is excreted in the urine, and can be used for diagnostic purposes. More detailed study revealed that transrenal DNA (Tr-DNA) belongs to a relatively low molecular-weight (150-250 bp) fraction, thereby requiring more careful attention to methods employed for purification and analysis. For example, here it is demonstrated that the QIAamp blood kit purifies primarily high molecular-weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
55
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 7 publications
1
55
0
2
Order By: Relevance
“…However, no study has addressed DNA degradation in saliva, and previous works have not systematically researched DNA degradation in serum, urine and saliva. In addition, the reported stability and degradation rates of DNA in bodily fluids vary significantly due to differences in extraction methods, PCR conditions and target sequences (Chiu et al, 2001;Fleischhacker et al, 2011;Su et al, 2004), and the nature of the nucleic acid measured (e.g., cell-free or cellular; mononucleosomes or oligonucleosomes).…”
Section: Introductionmentioning
confidence: 97%
“…However, no study has addressed DNA degradation in saliva, and previous works have not systematically researched DNA degradation in serum, urine and saliva. In addition, the reported stability and degradation rates of DNA in bodily fluids vary significantly due to differences in extraction methods, PCR conditions and target sequences (Chiu et al, 2001;Fleischhacker et al, 2011;Su et al, 2004), and the nature of the nucleic acid measured (e.g., cell-free or cellular; mononucleosomes or oligonucleosomes).…”
Section: Introductionmentioning
confidence: 97%
“…When DNA from paired urine and tissue sections (20 patients with either CRC or adenomatous polyps) were analyzed for the K-RAS mutation, an 83 % concurrence of mutated urine cfDNA and its corresponding disease tissue was obtained. The authors proposed that apoptotic cells were the source of the cfDNA [54]. Moulière and Thierry [65] demonstrated that CRC K-RAS fragments isolated from peripheral blood tended to be smaller than 100 bp, and given that the study of Su et al was based upon fragments of 150-250, it would be of interest to determine if smaller fragments could be present in urine and in high abundance.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 98%
“…Human urine contains, sub-microgram per milliliter amounts of cfDNA of between 150 and 250 bp [54]. A comparison was made of the mutated K-RAS sequences present in DNA isolated from tumor, blood and urine obtained from a CRC patient with a mutation in codon 12 of the K-RAS proto-oncogene.…”
Section: Colorectal Cancer (Crc)mentioning
confidence: 99%
See 1 more Smart Citation
“…These fragments are known as transrenal DNA (TrDNA) (47)(48)(49). Recently, a capillary electrophoresis TrDNA test that targets the E1 region of the HPV genome for the detection of hrHPV demonstrated high sensitivity and modest specificity for urine-based detection of cervical precancerous lesions (50).…”
Section: Discussionmentioning
confidence: 99%